2018
DOI: 10.1002/joa3.12075
|View full text |Cite
|
Sign up to set email alerts
|

The deeper the pouch is, the longer the radiofrequency duration and higher the radiofrequency energy needed—Cavotricuspid isthmus ablation using intracardiac echocardiography

Abstract: BackgroundThe aim of this study was to explore whether the pouch depth influenced the radiofrequency (RF) duration and total delivered RF energy for cavotricuspid isthmus (CTI) ablation and define the cutoff value for a deep pouch‐specified ablation strategy.MethodsThis study included 94 atrial fibrillation (AF) patients (56 males, age 68 ± 8.0 years). With intracardiac echocardiography, the isthmus length and pouch depth were precisely measured. After a standard AF ablation, all patients underwent the CTI abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
1
13
1
Order By: Relevance
“…In this study, CTI of less than 4.1 mm depth was an independent predictor for the first-pass success of CTI ablation. This cut-off value is similar to the <3.9 mm CTI depth necessary for knuckle curve ablation reported by Shimizu et al [13]. Consistent with a previous report, a lower first-pass success rate and longer procedural time were observed in the concave CTI cases.…”
Section: Cti Depth and First-pass Successsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, CTI of less than 4.1 mm depth was an independent predictor for the first-pass success of CTI ablation. This cut-off value is similar to the <3.9 mm CTI depth necessary for knuckle curve ablation reported by Shimizu et al [13]. Consistent with a previous report, a lower first-pass success rate and longer procedural time were observed in the concave CTI cases.…”
Section: Cti Depth and First-pass Successsupporting
confidence: 90%
“…The widely spaced double potential was also confirmed. If incomplete conduction block was suspected near the IVC, the ablation catheter would be deflected by more than 90 ° to ablate the interior of the pouch (Figure 1) [13].…”
Section: Ablation Methodsmentioning
confidence: 99%
“…The usage of ICE enabled direct visualization and a detailed assessment of the CTI anatomy. The ICE permitted to assess real contact between the tissue and the tip catheter, to improve the precision of the RF line with a merged isthmus and continuous monitoring of the pericardium and to prevent the “steam pop” showing the increased bubbles production during RF before that steam pop occurred 18,19 . Furthermore, anatomic CTI variations represented by the presence of a flat isthmus, pouch, long CTI, and prominent Eustachian ridge/valve have been shown to be the factors related to a longer RF duration 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Shimizu et al reported that the depth of the pouch was related to the RF duration and energy required to create a CTI block line, and the usefulness of knucklecurve ablation inside the pouch. 2 The use of intracardiac echocardiography is reported to be useful to detect CTI pouch in difficult cases. 3 In our case, we could not notice the existence of the prominent CTI pouch and failed to create a complete CTI block line during the first session.…”
Section: Discussionmentioning
confidence: 99%
“…A CTI pouch is mainly seen in the medial side of the CTI 1 and is known to complicate the creation of a CTI block line. Shimizu et al reported that the depth of the pouch was related to the RF duration and energy required to create a CTI block line, and the usefulness of knuckle‐curve ablation inside the pouch 2 . The use of intracardiac echocardiography is reported to be useful to detect CTI pouch in difficult cases 3 .…”
Section: Discussionmentioning
confidence: 99%